La gestión estratégica de una política de educación integral para alumnos sobresalientes: el caso de la Escuela de Talentos del Callao - Luna Domínguez, Araceli (2018)
In the last decades, education has become one of the fundamental and critical tasks of the national, regional and local levels of government. In this, the importance of the regional intervention is transcendental for the strategic promotion of educational development that allows the country to take advantage of the potential of its student population. This article seeks to describe how the public policy of integral education for outstanding students influences the sustainable development of a regional government. For this, the article is divided into two sections. In the first one, the influence between a public educational policy and the development of a regional government is explained, exposing, in addition, the characteristics of a comprehensive education for outstanding students as a strategy for regional institutional development. The second section describes, through the case of the Escuela de Talentos del Callao, the functioning of the integral educational development of the outstanding students as a public educational policy of the Callao region; also, we describe how this has generated sustainable institutional development at different levels . Finally, we analyze the relationship between the revised conceptual framework and the particular case of the talent school.